1996
DOI: 10.1143/jjap.35.4633
|View full text |Cite
|
Sign up to set email alerts
|

Linear and Nonlinear Optical Properties of CdS and CdSe Nanoparticles Stabilized with Poly(N-vinyl-2-pyrrolidone)

Abstract: CdS and CdSe nanoparticles were prepared in organic solvents in the presence of poly(N-vinyl-2-pyrrolidone) (PVP). PVP plays an essential role in preventing the flocculation of concentrated nanoparticles (stabilizing effect), and in controlling the particle size under the influence of the solvent used. FT-IR measurements were performed to study the effect of the functional groups of PVP on particle size control at molecular levels. The PVP-coated CdS and CdSe nanoparticles obtained were dispersed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…. This width variation is due to adsorption of CdSe NP on the surface of PVP which prevents the self association of lactam [29].…”
Section: Ftir Spectroscopymentioning
confidence: 99%
“…. This width variation is due to adsorption of CdSe NP on the surface of PVP which prevents the self association of lactam [29].…”
Section: Ftir Spectroscopymentioning
confidence: 99%
“…The investigations on the nonlinear optical properties of semiconductor nanocrystals have focused mainly into the thirdorder optical nonlinearity (or second hyperpolarizability γ). 1,2,[9][10][11][12][13][14][15][16][17][18][19] A large enhancement of this optical nonlinearity because of size quantization of the exciton motion has been predicted by Nakamura et al 9 and by Banyai et al 10 Although some * To whom correspondence should be addressed. E-mail: dvp@ npd.ufpe.br.…”
Section: Introductionmentioning
confidence: 99%
“…This leads to more absorption of electrons from the trap levels to the conduction bands [23]. Mathew et al [24] has also reported that the involvement of deep trap state level is the source of free-carriers in core/shell nanomaterials.…”
Section: Page 11 Of 24mentioning
confidence: 99%